(untitled) (Baghdad Science Journal, 2024)
Customers are arriving at the system in bulk according to the Poisson process with rate λ1. The batch service process is split into two phases called first essential service (FES) and second essential service (SES) with minimum server capacity ′a′ and maximum server capacity ′b′. Customer who requires feedback after SES completion will be taken immediately for service by the server with probability β.